Tinjauan Yuridis Terhadap Kejahatan Siber dan Perlindungan Data Pribadi - David Tendean; William Susanto (Legal Note, 2025)
The rapid development of information and communication technology has had a significant impact on global society, including in Indonesia. Behind the benefits it offers, this digital transformation also presents serious risks in the form of cybercrime, one of which is the violation of personal data. Crimes such as identity theft, account hacking, and the unauthorized dissemination of personal information have become increasingly prevalent threats. This indicates that the protection of personal data is becoming more crucial, both from technical and legal perspectives. This study aims to normatively examine the forms of cybercrime related to personal data breaches and the effectiveness of existing regulations in providing legal protection. The research is conducted using a normative juridical approach by analyzing relevant legislation, such as Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law) and Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). The analysis shows that although there is a legal basis in place, its implementation still faces several challenges, including weak law enforcement, inadequate digital infrastructure, and low public awareness regarding the importance of protecting data privacy. Considering the complexity of the issues and the highly dynamic technological developments, this study recommends the need for the refinement of national legal policies to be more adaptive and progressive. Synergy among institutions, strengthening the capacity of law enforcement in digital forensics, and increasing public digital literacy are strategic steps toward building a robust and equitable personal data protection system. Only through a comprehensive and responsive legal approach that keeps pace with the times can the security of personal data in the digital realm be effectively ensured.